Advances in management accounting - Akroyd, Chris (Advances in management accounting, 2024)
Volume 36 of Advances in Management Accounting uses a variety of methods, from experiments and case studies to surveys, to build upon existing knowledge within the management accounting discipline. Containing a diverse range of authors from around the world, this publication focuses on theoretically sound and practical research which has a cutting-edge and wide-reaching appeal to academics and practitioners. Showcasing chapters on, strategic accounting practices and performance management, this edited collection will appeal to both management accounting academics and professionals. Topics analyzed include the effects of organizational culture, manager narcissism, and misreporting, along with the impacts of entrepreneurial cognitive configurations and compensation setting processes. Advances in Management Accounting (AIMA) publishes thought-provoking volumes that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. The series seeks thoughtful, well-developed articles on a variety of current topics in management accounting, broadly defined. AIMA seeks to publish commentaries on research methodology and new management accounting areas of interest as well as papers using research methods including survey research, field tests, case studies, experiments, meta-analyses, and modeling.